Empowerment of siwalan roomie processing small and medium-sized enterprises (SMEs) through strengthening good manufacturing practice (GMP) in Tuban Regency - Putri, WDR; Andayani, W; Sutan, S M; Rucitra, A L; Firdausyi, I A (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Siwalan is palm type plant, which one of the prime agricultural commodities in the Tuban Regency. Siwalan production has increased from year to year. Abundant production provides great potential for siwalan farmers and groups of siwalan processed enterprises for product diversification. Legen drinks and siwalan fruit are known as typical souvenir products of Tuban and are favored by local tourists. However, some problems related to product hygiene and low storage are becoming the challenges for the siwalan farmers. So far, technological innovation has not been implemented on the processing of legen or siwalan fruit. Furthemore, the marketing development is limited and has not been able to enhance the local community. The purpose of this activity was to examine the relationship between aspects of attitude towards food security with aspects of business performance and the importance of strengthening Good Manufacturing Practice (GMP). The results showed that there is no significant relationship between aspects of attitude towards food safety with aspects of business performance. The findings also confirmed that the food safety aspect was ignored, especially in legen beverage production process. Some producers added food additives to extend the shelf life of legen. Such practice influenced the taste of legen and the food security. Therefore, socialization and training related to GMP is a key factor for improving business performance and achieving sustainable development.